STRUKTUR MODAL PADA USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN MANOKWARI - Nugroho Riyanto; Rintar Agus Simatupang; Louis Soemadi Bopeng (Fakultas Bisnis UKDW, 2017)
Micro Small and Medium Enterprises (SMEs) is a business that is able to reduce the unemploymentrate in the district of Manokwari. The number of SMEs from year to year the numbers continue toincrease, but in the course of time is less developed. Most successful businesses are growing, due tothe limited capital to fund operations. Fulfillment of the capital do business owners throughborrowing at the bank. Banks in lending charge a large interest expense, there by aggravating thebusiness owner if the loan amount is too large. This study aims to analyze the influence of assetstructure, company size and profitability of the capital structure. The sampling technique this studyusing purposive random sampling, with 87 SMEs. Based on the results of the analysis indicate thatvariable asset structure, company size, and profitability influence simultaneously and partially to thecapital structure. For business owners should be before the structure of assets pledged as collateralfor a loan should pay attention to the amount of borrowed funds in accordance with the value of theexisting asset structure, so that business activities more efficient and effective.Keywords: capital structure, asset structure, company size, profitability